P732 Disability in older IBD patients. (16th January 2018) - Asscher, V; Meijer, L; Waars, S; Slagboom, J; Van der Meulen- de Jong, A; Mooijaart, S; Maljaars, J
Abstract: Background: The prevalence of inflammatory bowel disease (IBD) among the elderly increases due to an increasing age of the population and an increasing incidence of IBD. Recently, attention has focused on the importance of reducing disability amongst IBD patients. Little is known about disability, and factors related to disability, in older IBD patients. The purpose of this study was to assess the influence of different geriatric measurements and IBD disease activity on IBD related disability measured with the IBD-Disability Index (IBD-DI) in a cohort of elderly IBD patients. Methods: Consecutive IBD patients aged ≥ 65 years were included. IBD-DI was used to determine disability (score 0–20: no disability, 20–35 mild disability, 35–50 moderate disability, 50–100 severe disability). The Geriatric 8 (G8) questionnaire was used for geriatric assessment, a lower G8 shows higher vulnerability and increased impairment. Physical frailty was measured using 4-meter gait speed and handgrip strength (HGS). HGS was corrected for age, gender and left- or right-handedness. IBD-related quality of life (QoL) was measured with the Short Inflammatory Bowel Disease Questionnaire (SIBDQ) which shows a lower QoL with a higher score. Incontinence was measured with the Vaisey Incontinence Scale (VIS) and disease activity was measured using Harvey-Bradshaw Index (HBI- for CD) and partial mayo Score (PMS- for UC). A multiple correlation analysis was performed, with IBD-DI as dependent factor. Results: A total of 135 patients were included (mean age 71.48 years), of which 73 (52%) had Crohn's disease. Mean disability was 19.4 (95%-CI 17.7–21.4). Seventy-two patients had no disability, 53 had mild and 6 had moderate disability. Only 1 patient had severe disability. Thirty (22.7%) patients had reduced HGS, and 59 had an aberrant G8, indicating frailty. A multiple regression was run to identify factors associated with disability (Table 1). The variables HBI, PMS, SIBDQ, VIS, G8 and HGS added statistically significantly to the model for disability. Conclusions: This study, using the IBD-DI, found a low degree of disability in our cohort of older IBD patients. Disease activity (HBI, pMS) was significantly related to disability. However, when looking at geriatric assessment, G8 and in particular handgrip strength were strongly related to the IBD-DI. These data show the importance of assessing geriatric components such as (physical) frailty, and not only remission status when aiming to reduce disability in older IBD patients